2002
DOI: 10.1002/ajmg.10248
|View full text |Cite
|
Sign up to set email alerts
|

Novel polymorphisms in the promoter region of the neurotrophin‐3 gene and their associations with schizophrenia

Abstract: Based on the neurodevelopmental hypothesis in the etiology of schizophrenia, neurotrophic factors may be involved in the pathogenesis of the illness. We searched for polymorphisms in the promoter region of the neurotrophin-3 (NTF3) gene by using denaturing high performance liquid chromatography (DHPLC). Six single nucleotide polymorphisms (SNPs) were found. When these polymorphisms were examined for association with schizophrenia, a weakly significant difference was observed in the genotype distribution of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…A genetic link between neurotrophins and schizophrenia is supported by the evidence that polymorphisms of the NT-3 and BDNF genes are associated with schizophrenia. [7][8][9] Lastly, findings that BDNF is decreased by factors correlated with first episode onset, such as stress 59,21 and estrogen withdrawal, 60 are also consistent with the putative BDNF role in schizophrenia. Interestingly, these stress-induced decreases in BDNF are blocked by 5-HT2 receptor antagonists, a receptor binding property of many neuroleptics.…”
Section: Animal Modelsmentioning
confidence: 53%
See 1 more Smart Citation
“…A genetic link between neurotrophins and schizophrenia is supported by the evidence that polymorphisms of the NT-3 and BDNF genes are associated with schizophrenia. [7][8][9] Lastly, findings that BDNF is decreased by factors correlated with first episode onset, such as stress 59,21 and estrogen withdrawal, 60 are also consistent with the putative BDNF role in schizophrenia. Interestingly, these stress-induced decreases in BDNF are blocked by 5-HT2 receptor antagonists, a receptor binding property of many neuroleptics.…”
Section: Animal Modelsmentioning
confidence: 53%
“…Studies on post-mortem Human Decreased BDNF concentrations in cortical areas and hippocampus of schizophrenic patients 4 Reduction of TrkB and BDNF-positive neurons in CNS 5 and BDNF in the serum 6 of schizophrenics Polymorphisms of BDNF gene associated with schizophrenia [7][8][9] Animal models…”
Section: Bdnf and Schizophreniamentioning
confidence: 99%
“…[46][47][48][49][50] Although several association studies have been conducted to investigate the association of NTF3 and GRIN2B with schizophrenia and alcohol dependence, the results have been inconclusive. [51][52][53][54] Regarding potential candidate genes from other regions, we will not discuss these in the present report because (1) they have been reported previously for possible association with nicotine and/or alcohol dependence in independent sample; (2) potential candidate genes for a few chromosomal regions were discussed in our recent report based on the AA sample; 20 and/or (3) a limited number of candidate genes are obvious on the basis of their functionality unless we are able to demonstrate their association experimentally, a consideration which is well beyond the scope of this report.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported a significant association between schizophrenia and a dinucleotide repeat (CA) n polymorphism in the first intron of the NTF3 gene: the 'A3' allele, (CA) 23 , was significantly more common in schizophrenics than in controls [4,5]. Subsequently, sev-eral studies obtained evidence supporting this association [6][7][8][9], although contradictive negative results have also been reported [10][11][12]. Interestingly, individuals with schizophrenia who carried the A3 allele had smaller hippocampi than those who did not [13].…”
Section: Introductionmentioning
confidence: 75%